Weathering of siderite in the polar conditions - Figura, Paulina; Manecki, Maciej; Rzepa, Grzegorz (Wydawnictwa AGH, 2014)
Rapid retreat and thinning of glaciers perturb balance of polar ecosystems. These processes influence global climate (Anderson et al. 2000, Płonka 2009).
Geology, Geophysics & Environment
Keywords: global climate; ecosystem; CO2